2012
DOI: 10.1007/s11845-011-0797-y
|View full text |Cite
|
Sign up to set email alerts
|

Fixation of tibial plateau fractures with synthetic bone graft versus natural bone graft: a comparison study

Abstract: Use of autologous or allogenic bone graft allows better recovery of long-term flexion, possibly due to reduced inflammatory response compared with synthetic bone composites. However, all other parameters, such as maintenance of joint reduction and subjective outcome measures were comparable with the use of hydroxyapatite calcium carbonate bone graft. This study shows that synthetic bone graft may be a suitable alternative in fixation of unstable tibia plateau fractures, avoiding risk of disease transmission wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 17 publications
0
18
0
2
Order By: Relevance
“…To maintain the reduction, the subchondral void is usually filled with cancellous autografts, allografts, or bone substitutes. 4 Autografting is associated with donor-site morbidity, risk of infection, increased surgical time and blood loss, 5 whereas allografting is associated with the risk of disease transmission, low initial stability in the metaphyseal defects, and inadequate incorporation of the graft to host bone. 6 The use of a raft screw construct in the subchondral bone through a locking plate can avoid these potential problems and provide support to the articular surface of the lateral and medial condyles of the proximal tibia, irrespective of bone quality and the type of fixation.…”
Section: Abstract: Bone Substitutes; Fracture Fixation Internal; Timentioning
confidence: 99%
“…To maintain the reduction, the subchondral void is usually filled with cancellous autografts, allografts, or bone substitutes. 4 Autografting is associated with donor-site morbidity, risk of infection, increased surgical time and blood loss, 5 whereas allografting is associated with the risk of disease transmission, low initial stability in the metaphyseal defects, and inadequate incorporation of the graft to host bone. 6 The use of a raft screw construct in the subchondral bone through a locking plate can avoid these potential problems and provide support to the articular surface of the lateral and medial condyles of the proximal tibia, irrespective of bone quality and the type of fixation.…”
Section: Abstract: Bone Substitutes; Fracture Fixation Internal; Timentioning
confidence: 99%
“…64,65 Residual symptomatology of moderate intensity is found in 40% of these patients, while 20% will report severe complaints. 40 Several studies have shown that even if accurate reduction is achieved, 30% of the patients will develop post-traumatic arthritis. 64,65 Even if ‘anatomical’ reduction is achieved, the incidence of reduction loss is significant and occurs in approximately 25% of the cases.…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…56 Several studies have shown no significant difference in the clinical outcomes between cases treated with autografts or allografts and bone graft substitutes. 39,40,42,43 It should be mentioned that any concomitant injuries, such as meniscal tears or ligament ruptures, should be addressed simultaneously as they can negatively compromise the final outcome. Satisfactory results do not always correlate with the radiological appearance, possibly due to the function of the menisci that can bear weight and relieve pressure over the lateral compartment…”
Section: Clinical Outcomesmentioning
confidence: 99%
“…Interestingly, 25 years after their definition that cells are one basic point of TE and while today approaches implanting (primarily) cell-free scaffolds (that are populated by the hosts' cells later) have been successfully applied in clinical applications (e.g., for bone, cartilage and skin) [50,[111][112][113], while cell-seeded scaffold strategies have so far failed both clinically and economically [8,35]. Natural tissues display a distinct highly organised macro-and micro-architecture with complex spatial distributions of various cell types and extracellular components.…”
Section: Future Outlook: Image-guided Tissue Engineering Additive Timentioning
confidence: 99%